2004
DOI: 10.1002/mop.20189
|View full text |Cite
|
Sign up to set email alerts
|

SAR affected by shapes and electrical properties of the human head exposed to a cellular phone

Abstract: ABSTRACT:The local maximum specific absorption rate (SAR)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…It is found that, the highest SAR value is obtained in the region of the skin near the handset. In addition, some other issues should be noted as well, as suggested by a comparison of the SARs induced in the realistic human-head model for the homogeneous and the inhomogeneous cases [30]. It is found that the constitutive parameters of a human head significantly affect the result of the SAR induced in homogeneous or inhomogeneous head models where the local maximum SAR induced in the homogeneous human-head model is larger than that induced in the inhomogeneous human head model.…”
Section: Interaction Between Handset and Human Hand-headmentioning
confidence: 95%
See 1 more Smart Citation
“…It is found that, the highest SAR value is obtained in the region of the skin near the handset. In addition, some other issues should be noted as well, as suggested by a comparison of the SARs induced in the realistic human-head model for the homogeneous and the inhomogeneous cases [30]. It is found that the constitutive parameters of a human head significantly affect the result of the SAR induced in homogeneous or inhomogeneous head models where the local maximum SAR induced in the homogeneous human-head model is larger than that induced in the inhomogeneous human head model.…”
Section: Interaction Between Handset and Human Hand-headmentioning
confidence: 95%
“…A study of how the SAR is affected by different shapes and electrical properties of the human head exposed to a cellular phone have been reported [30]. The results showed that the shape of the human head plays a minor role in calculating the SAR induced in human head models.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained in Figure 6 indicate that, the resulting SAR values for the smart handset in different scenarios are under the limits set by IEEE C95.1: 2005 or ICNIRP standards. In addition, some other issues should be noted as well, as suggested by a comparison of the SARs induced in the realistic human-head model for the homogeneous and the inhomogeneous cases [24]. It is found that the constitutive parameters of a human head significantly affect the result of the SAR induced in homogeneous or inhomogeneous head models where the local maximum SAR induced in the homogeneous human-head model is larger than that induced in the inhomogeneous human head model.…”
Section: The Impact Of the Handset On Sarmentioning
confidence: 95%
“…A study of how the SAR is affected by different shapes and electrical properties of the human head exposed to a cellular phone has been reported [24]. The results showed that the shape of the human head plays a minor role in calculating the SAR induced in humanhead models.…”
Section: Introductionmentioning
confidence: 99%
“…According to Chen and Yang (2004), the local SAR was lowered by approximately 40% when distance increased from 1 to 2 cm at 900 MHz and by about 60% at 1800 MHz. The size of reduction was the same with the homogeneous phantom.…”
Section: Sources Of Error In Epidemiological Studiesmentioning
confidence: 97%